The effect of election beam irradiation on the quality of hydrolysed collagen and cell viability - Nik Rabi'atul Adawiyah Nik Zulkifeli (2018)
The purpose of this study was to evaluate the effect of electron beam irradiation atdifferent dosages towards the quality of hydrolysed collagen samples from Oreochromis mossambicus’sscales. Hydrolysed collagen samples powder were irradiated using electron beam at doses of 5, 10,15 and 20 kGy. After being irradiated, samples were individually vacuum-packaged and stored at 4°Cfor four weeks. Then, the total number of coliform, yeast and mould, pH, macronutrients of samples,and molecular weight of the samples’ protein were investigated. This study also determined theeffect of hydrolysed collagen samples at different concentrations towards the viability andproliferation of skin fibroblast primary cell. The results showed that total number of coliform,yeast and mould decreased with the increment of irradiation dosage, but, no coliform, yeast andmould growth in 15 and 20 kGy samples. Meanwhile, the D10 value of coliform is 14.43 kGy whilstyeast and mould is13.76 kGy. The samples’ pH values and macronutrients evaluation did not show any significantdifferences between non-irradiated and irradiated samples. Sodium dodecyl sulphate polyacrylamidegel electrophoresis (SDS-PAGE) separated two bands of protein between 17.75 to 23.5 kDa. It alsoshowed that electron beam irradiation dosage did not cause any substantial change ofelectrophoretic pattern on molecular weight of hydrolysed collagen. The concentration of hydrolysedcollagen between 4 mg/mL to 10 mg/mL has increased the viability and proliferation of normal skinfibroblast primary cell. As a conclusion, the results suggest that electron beamirradiation is useful in improving microbial safety without impairing the quality of hydrolysedcollagen. The implication of this study is hydrolysed collagen from O.mossambicus’s scales can beused to increase the number and proliferation of skinfibroblast cell and would be essential for any skin care and pharmaceutical use.